PHYLACINE 1.2: The Phylogenetic Atlas of Mammal Macroecology. Issue 11 (1st October 2018) - Faurby, Søren; Davis, Matt; Pedersen, Rasmus Ø.; Schowanek, Simon D.; Antonelli1, Alexandre; Svenning, Jens‐Christian
Abstract: Data needed for macroecological analyses are difficult to compile and often hidden away in supplementary material under non‐standardized formats. Phylogenies, range data, and trait data often use conflicting taxonomies and require ad hoc decisions to synonymize species or fill in large amounts of missing data. Furthermore, most available data sets ignore the large impact that humans have had on species ranges and diversity. Ignoring these impacts can lead to drastic differences in diversity patterns and estimates of the strength of biological rules. To help overcome these issues, we assembled PHYLACINE, The Phylogenetic Atlas of Mammal Macroecology. This taxonomically integrated platform contains phylogenies, range maps, trait data, and threat status for all 5, 831 known mammal species that lived since the last interglacial (~130, 000 years ago until present). PHYLACINE is ready to use directly, as all taxonomy and metadata are consistent across the different types of data, and files are provided in easy‐to‐use formats. The atlas includes both maps of current species ranges and present natural ranges, which represent estimates of where species would live without anthropogenic pressures. Trait data include body mass and coarse measures of life habit and diet. Data gaps have been minimized through extensive literature searches and clearly labelled imputation of missing values. The PHYLACINE database will be archived here as well as hosted online so that users may easily contribute updates and corrections to continually improve the data. This database will be useful to any researcher who wishes to investigate large‐scale ecological patterns. Previous versions of the database have already provided valuable information and have, for instance, shown that megafauna extinctions caused substantial changes in vegetation structure and nutrient transfer patterns across the globe.